2020
DOI: 10.3389/fmolb.2020.00049
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinase Inhibitor b-AP15 Attenuated LPS-Induced Inflammation via Inhibiting ERK1/2, JNK, and NF-Kappa B

Abstract: b-AP15 is a deubiquitinase (DUB) inhibitor of 19S proteasomes, which in turn targets ubiquitin C-terminal hydrolase 5 (UCHL5) and ubiquitin-specific peptidase 14 (USP14). Nuclear factor kappa B (NF-κB) is closely linked to cellular response in macrophages when the organism is in the state of microbial infection, and it acts as a vital part in the mechanism of inflammatory reaction. However, the molecular mechanism by which DUB inhibitors, especially b-AP15, regulates inflammation remains poorly understood. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…b-AP15 has previously been shown to inhibit several signaling pathways associated with proliferation and survival, such as IκB-NFκB, ERK/MAPK, and STAT3 [ 43 45 ]. Under basal conditions, treatment with varying concentrations of b-AP15 had minimal effect on the phosphorylation or expression of IKKα, IKKβ, RELA, ERK or STAT3, except at b-AP15 concentrations ≥500 nM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…b-AP15 has previously been shown to inhibit several signaling pathways associated with proliferation and survival, such as IκB-NFκB, ERK/MAPK, and STAT3 [ 43 45 ]. Under basal conditions, treatment with varying concentrations of b-AP15 had minimal effect on the phosphorylation or expression of IKKα, IKKβ, RELA, ERK or STAT3, except at b-AP15 concentrations ≥500 nM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the only USP family that can reversibly bind the 19S regulatory particle of the proteasome, USP14 plays a critical role in regulating the inflammation progression in various diseases, such as lung injury and atherosclerosis. 16,38 For example, Zhang et al 20 In addition to the number of inflammatory cells from the blood, the number of activated resident inflammatory glial cells, such as microglial cells and astrocytes, was markedly reduced after IU1 treatment. Furthermore, the release of cytokines from inflammatory cells was significantly decreased after USP14 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…USP14 is a well‐studied DUB belonging to the UPS family that plays dual roles in regulating protein degradation 15 . Dysregulated USP14 expression leads to various pathologies, such as inflammation, apoptosis, and even ferroptosis, by either promoting or inhibiting protein degradation, which results in cancer, neurobiological diseases, and atherosclerosis‐related diseases 16–20 . USP14 was first reported to be expressed on the neurons and to negatively regulate neuronal survival in the brain 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Our data coincides with studies by Qu et al ( 32 ) as well as Kummari et al ( 33 ) that have shown that UCHL5 is required for NLRP3 inflammasome activation in mycobacterial and salmonella infections, respectively. Zhang et al also showed that inhibition of UCHL5 blocked TNF-α and IL-6 induction in lipopolysaccharide (LPS)-treated THP-1 macrophages ( 34 ). Our study indicates that UCHL5 is also important for NLRP3 activation during viral infection.…”
Section: Discussionmentioning
confidence: 99%